Their floods and Our floods: News values of flood photo galleries of Associated Press and Xinhua News Agency. (June 2023) - Yu, Hailing; Chen, Guangfeng
This study investigates how floods are presented as newsworthy in the photo galleries of Associated Press (AP) and Xinhua News Agency (Xinhua), two news outlets with different cultural and political backgrounds. A distinction is made between international floods, that is, Their floods, and domestic floods, that is, Our floods. The data consists of around 1500 photo-caption complexes. The analysis adopts the framework of Discursive News Values Analysis. The findings show a similar tendency to highlight Negativity, Impact, Personalization and Superlativeness in presenting Their floods by AP and Xinhua, though the two differ in Proximity and Positivity. By contrast, Our floods are presented differently. Negativity, Impact and Personalization are foregrounded in AP's presentation of floods in the United States, whereas Xinhua's presentation of floods in China gives prominence to Negativity, Positivity, Personalization and Superlativeness. The study is significant for its attention to cross-cultural comparison and the genre of online photo galleries.